Effectively Improved SiO2-TiO2 Composite Films Applied in Commercial Multicrystalline Silicon Solar Cells. (12th September 2013) - Yang, Chih-Hsiang; Lien, Shui-Yang; Chu, Chia-Ho; Kung, Chung-Yuan; Cheng, Tieh-Fei; Chen, Pai-Tsun
Abstract : Composite silicon dioxide-titanium dioxide (SiO2 -TiO2 ) films are deposited on a large area of 15.6 × 15.6 cm 2 textured multicrystalline silicon solar cells to increase the incident light trapped within the device. For further improvement of the antireflective coatings (ARCs) quality, dimethylformamide (DMF) solution is added to the original SiO2 -TiO2 solutions. DMF solution solves the cracking problem, thus effectively decreasing reflectance as well as surface recombination. The ARCs prepared by sol-gel process and plasma-enhanced chemical vapor deposition (PECVD) on multicrystalline silicon substrate are compared. The average efficiency of the devices with improved sol-gel ARCs is 16.3%, only 0.5% lower than that of devices with PECVD ARCs (16.8%). However, from equipment depreciation point of view (the expiration date of equipment is generally considered as 5 years), the running cost (USD/watt) of sol-gel technique is 80% lower than that of PECVD method for the first five years and 66% lower than that of PECVD method from the start of the sixth year. This result proves that sol-gel-deposited ARCs process has potential applications in manufacturing low-cost, large-area solar cells.